Characterizing the trend of channel braiding of a tropical transboundary river using spatial growth component analysis and ARIMA model. Issue 7 (1st October 2022) - Deep Saha, Ujwal; Mannan Saheb, Abdul; Islam, Aznarul; Deb Barman, Suman; Dutt, Sanjana; Reza Md. Towfiqul Islam, Abu
Highlights: Trend of channel braiding of a tropical river is assessed using braiding index, channel count and length indices. The planform indices portray allometric growth patterns during the observation period (1990–2020). The simulation of bar growth using ARIMA model indicates an oscillatory behaviour controlled by local morphotectonics. The future forecast of bar growth for 2030 and 2050 has been tested with the RMSE and BIC. The characterization of complex braiding patterns implies significant regional policy implications. Abstract: Channel braiding is one of the fundamental fluvial processes in the context of sediment-energy nexus. The present study intends to simulate the channel braiding pattern of a tropical river (Jaldhaka River) on the Himalayan foreland plains. The grain size of the bed material in the Jaldhaka River decreases with distance from the mountain front, as does the surface gradient from the piedmont plains to the northern alluvial plains accompanied by the development of alluvial fans. Such assemblage results in multiple facets of hydro-geomorphic controls on channel planform dynamicity. This study is one of the pioneering attempts to characterize the spatial and temporal trend of channel braiding in any river running through the foreland region of the Sikkim-Bhutan Himalayas. The type of channel braiding is determined by the three indices – (1) Braiding Index (BI*), (2) Channel Count Index (BI), and (3) Channel Length Index (Pt ), in cases where no gradual and uniform trend of development has been seen. The spatial allometric growth of the channel braiding and time series association using the ARIMA model was examined on the twenty stretches of the river. The results depict nonuniformity in planform development with distance downstream during a 30-year time span (1990–2020). The nature of the planform value distribution concerning all three applied indices has projected a polynomial trend where certain intermediate channel segments break the general trend of the braiding intensity with downstream distance. Since the downstream braiding intensity of the Jaldhaka River hasn't decreased either linearly or exponentially, we were unable to find any significant relationship of it with surface gradient. The nature and association of the channel braiding of the Jaldhaka River point towards the influence of local controls (e.g. river terracing on the upper part and faultline controls in the middle part) on channel planform dynamicity. The prediction of channel braiding for 2030 and 2050 coupled with the model fitted with RMSE, and BIC bears great significance in revealing the future bar growth which may be useful for the different planners and stakeholders concerned with the river basin development.